2018
DOI: 10.1039/c7dt04477a
|View full text |Cite
|
Sign up to set email alerts
|

Ligand modification of UiO-66 with an unusual visible light photocatalytic behavior for RhB degradation

Abstract: A series of isostructural UiO-66-X (X = H, NH, Br, (OH), (SH)) catalysts have been successfully synthesized by modifying different functional groups on the ligand. The effects of the ligand modification of UiO-66 were investigated for their photocatalytic activity of Rhodamine B degradation under visible light. Surprisingly, UiO-66-NH and UiO-66-(OH) which have narrow bandgaps and excellent visible light absorption do not show outstanding photocatalytic performances compared to UiO-66 and UiO-66-Br. Electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 63 publications
6
64
0
Order By: Relevance
“…Nevertheless, as occurred with N-donor ligands, although the NH 2 -MOFs had narrow band gaps, their photocatalytic activity did not stand out for dyes removal. Mu et al demonstrated that UiO-66-NH 2 had worse photocatalytic performance for RhB degradation than UiO-66 in spite of its lower band gap [196].…”
Section: Photodegradation Of Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as occurred with N-donor ligands, although the NH 2 -MOFs had narrow band gaps, their photocatalytic activity did not stand out for dyes removal. Mu et al demonstrated that UiO-66-NH 2 had worse photocatalytic performance for RhB degradation than UiO-66 in spite of its lower band gap [196].…”
Section: Photodegradation Of Dyesmentioning
confidence: 99%
“…Unfortunately, MOFs have relatively inferior stability than other photocatalysts, such as those based on TiO2, CdS, BiVO4, g-C3N4, and their heterojunctions. Their instability can be mainly related to the self-dissolution of some components into the aqueous reaction medium, and some irreversible reaction of metal clusters and/or the organic linkers with some component (reactant, products, or byproducts) of the water medium [166,196,245]. The main factor controlling the stability of MOFs in water is the strength of the metal-ligand bonds, although the crystallinity, metal-ligand coordination geometry, and porosity must be also considered [119,246].…”
Section: Stability and Reusability Of Mofs During Water Purification mentioning
confidence: 99%
“…Nevertheless, in some cases, although the NH2-MOFs had narrow band gaps, their photocatalytic activity did not stand out. In different works it has been concluded that it is not only important to generate electrons and holes, but to keep them separate avoiding the recombination [158,189].…”
Section: Photodegradation Of Dyesmentioning
confidence: 99%
“…[ 5 ] From an optical standpoint, the effect of different functional groups on the linker on optical absorptions of Zr‐based MOFs has been investigated. [ 6 ] In the absence of chromophores, the ZrBDC retains a high absorption in UV range with the band edge of 300–350 nm, corresponding to the wide bandgap and insensitive to the visible‐infrared region. [ 6,7 ] In addition to high selectivity in the UV spectrum, lifespan of photodetector using wide‐bandgap material instead of commercial narrow‐bandgap ones (such as Si with E g = 1.12 eV) as a light‐harvesting constituent is expected to be significantly extended under prolonged exposure to high‐energy UV irradiation owing to its high stability.…”
Section: Introductionmentioning
confidence: 99%